2016
DOI: 10.1186/s12935-016-0280-y
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of glycolytic enzyme hexokinase II (HK2) suppresses lung tumor growth

Abstract: BackgroundThe most common genetic changes identified in human NSCLC are Kras mutations (10–30 %) and p53 mutation or loss (50–70 %). Moreover, NSCLC with mutations in Kras and p53 poorly respond to current therapies, so we are trying to find a new target for the treatment strategies.MethodsFlow cytometry, crystal violet staining and immunoblotting were used to assess cell cycle arrest, proliferation and apoptosis in lung cancer cell lines after 2-DG treatment and lentivirus infection by shRNA knock down. IHC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 48 publications
4
56
0
Order By: Relevance
“…Similarly, expression and activity of HK2 has been observed to be upregulated in nearly all types of cancers (32). Notably, enhanced activity of HK2 is required for the initiation and maintenance of K-Ras driven cancers, and its inhibition is shown to reduce tumor growth both in vitro and in vivo (39). There is also evidence to suggest the utility of HK2 as a prognostic marker in PDAC patients (40).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, expression and activity of HK2 has been observed to be upregulated in nearly all types of cancers (32). Notably, enhanced activity of HK2 is required for the initiation and maintenance of K-Ras driven cancers, and its inhibition is shown to reduce tumor growth both in vitro and in vivo (39). There is also evidence to suggest the utility of HK2 as a prognostic marker in PDAC patients (40).…”
Section: Discussionmentioning
confidence: 99%
“…A glycolytic metabolism is highly correlated with tumor proliferation. Knockdown or pharmacological inhibition of glycolytic enzymes reduces growth in a variety of cancers . Forced induction of respiration has led to slower growth rates both in vitro and in vivo .…”
Section: Glycolysis Reduces Overabundant Ros To Increase Survival Andmentioning
confidence: 99%
“…Knockdown or pharmacological inhibition of glycolytic enzymes reduces growth in a variety of cancers. [50][51][52][53] Forced induction of respiration has led to slower growth rates both in vitro and in vivo. 6,54,55 Conversely, lower oxidative phosphorylation due to mutant mitochondria increases both glycolysis and growth.…”
Section: Glycolysis Reduces Overabundant Ros To Increase Survival Andmentioning
confidence: 99%
“…HK plays a dominant role in glycolysis by promoting the coupling of ATP with glucose phosphorylation. Wang et al showed that silencing HK2 expression and inhibiting the expression of 2‐DG inhibited tumor cell proliferation and tumor growth . As a core factor of PI3K‐AKT‐mTOR signaling pathway, AKT plays a prominent role in increasing glucose uptake of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed that silencing HK2 expression and inhibiting the expression of 2-DG inhibited tumor cell proliferation and tumor growth. 23 As a core factor of PI3K-AKT-mTOR signaling pathway, AKT plays a prominent role in increasing glucose uptake of tumors. GSK2141795, as an AKT inhibitor, has significant antitumor effect.…”
Section: Du Et Almentioning
confidence: 99%